Influence of fruit maturity and variety on seasonal postharvest fungal diseases and vascular streaking in California Avocados - Boris X. Camiletti; Claudia M. Asensio; Thiago A. Carraro; Giorgio Gusella; Eric D. Focht; Roman Pandey; Themis J. Michailides; Mary Lu Arpaia (PLoS ONE, 2026)
This study evaluated the avocado varieties ‘Hass’, ‘GEM’, ‘Luna UCR’, ‘Eugenin’, ‘Flavia’, I27EG, I55B, I49LB, I54J, and I73WL to determine seasonal dry matter (DM) patterns and assess how harvest timing, storage duration, and variety influenced stem-end rot, body rot, vascular streaking, and fruit susceptibility. Fungal pathogens associated with postharvest decay were identified using morphological characterization and multilocus phylogenetic analyses based on ITS, tub2, tef1-α, GAPDH, and MAT1–2 regions. Four Neofusicoccum species ( N. australe , N. luteum , N. nonquaesitum , and N. parvum ), one Colletotrichum species ( C. perseae ), and two Diaporthe species ( D. baccae and D. foeniculina ) were identified from decayed avocado fruits. Susceptibility tests confirmed that N. nonquaesitum was the most aggressive pathogen on avocado fruit, followed by C. perseae and D. foeniculina . The diversity of pathogens causing postharvest rot highlighted the complexity involved in managing stem-end rot and body rot in avocado fruits. Seasonal patterns of dry matter (DM) accumulation were identified for new varieties, aiding in establishing these standards. The study explored the seasonal variation in DM percentages across different avocado varieties and their correlation with disease severity. Results showed that this parameter can help prevent fungal disorders in some varieties. This finding emphasized the importance of adhering to both minimum and potentially maximum maturity standards to minimize fruit diseases and disorders and optimize postharvest performance. Additionally, the seasonality of stem-end and body rots in California avocados appears to be more associated with the inherent susceptibility of the fruits at harvest time than with environmental factors. Overall, general seasonal patterns were difficult to determine, as final postharvest disease intensity depended on the variety and the disease.